Codzienne sprawy w kręgu dworu Marii z Kątskich Potockiej (zm. 1768). Zarys problemu na podstawie korespondencji kierowanej do starościny lwowskiej w latach 1765-1766 - Kicińska Urszula (Saeculum Christianum, 2022)
Marianna Potocka née Kątska (1722-1768), starostess of Lviv, is an extraordinary figure. She is considered a precursor of the Polish Enlightenment, a bibliophile, and an art patroness. She inherited a huge fortune of the Kątski, Denhoff, and Szczuka families, which became the foundation of the Potocki family’s later economic power. Together with her husband, Eu-stachy Potocki (1720-1768), she was engaged in large-scale business and patronage activities. Still, little is known about daily life at the Potocki’s manor. Therefore, the article focuses on presenting her activities, especially in the areas of managing her extensive estates, raising and educating her children, and charitable activities. These factors created her everyday life.